Analisis Kebijakan dan Strategi Bisnis PT Avo Inovation Technology - Andarini, Sonja; Ikaningtyas, Maharani; Firjatullah, Cynarawita; Candra , Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of the digital era is growing rapidly until now. Digitalization has spread to various fields, especially in the business sector. Almost all companies, from small to large, use digitalization as their marketing policy and strategy. This study aims to analyze the influence of the digital era on company business policies and strategies. The research method used is descriptive qualitative. The researcher conducted an analysis referring to the relevant data. Examines the theory with the influence between variables from data collected from journals and articles for the last five years. The results of this study indicate that the digital era has an influence on the company's business policies and strategies